2004
DOI: 10.1016/s1525-1578(10)60519-3
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Polymerase Chain Reaction Nucleobase Quenching Assay to Detect the 1-kbp Deletion in CLN3 That Causes Batten Disease

Abstract: Batten disease is an autosomal recessive disorder also known as juvenile neuronal ceroid lipofuscinosis. The most common mutation for this disease is an approximately 1-kbp deletion in the CLN3 gene, which accounts for about 80 to 85% of the mutation load. We developed a rapid assay for this mutation using the PCR to produce amplicons that are detected by nucleobase quenching of the fluorescent signal from a probe labeled with a fluorescent dye. The probe overlaps the deletion breakpoint and is completely base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Thirteen children were homozygous for the common deletion in the CLN3 gene. The common deletional mutation in the CLN3 gene was analyzed by using methodology previously described by this research group (Rothberg et al 2004). Two children were heterozygous for the deletion with a novel mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen children were homozygous for the common deletion in the CLN3 gene. The common deletional mutation in the CLN3 gene was analyzed by using methodology previously described by this research group (Rothberg et al 2004). Two children were heterozygous for the deletion with a novel mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the common deletion in the CLN3 gene was done as previously described. 12 If the subject was not homozygous for the common deletion, additional sequencing of the CLN3 gene was performed.…”
Section: Methods Protocol Approval and Subject Consentsmentioning
confidence: 99%
“…We attempted to design assays using a homogeneous PCR platform that uses differential melting of an oligodeoxyribonucleotide probe to distinguish the alleles, and nucleobase quenching of a fluorescent dye linked to the probe to generate the signal, because we have found this method useful for low-volume genotyping in several situations including detection of the most common mutation in the CLN3 gene (Rothberg et al, 2004).…”
Section: Optimization Of Nucleobase Quenching Methodsmentioning
confidence: 99%
“…We made use of a strategy that employs PCR, differential melting of a fluorescently labeled oligodeoxyribonucleotide probe to distinguish the alleles, and nucleobase quenching to detect probe hybridization (Crockett and Wittwer, 2001). We have found that this strategy is useful for low-volume genotyping for rare diseases (Rothberg et al, 2004;McClaskey et al, 2005).…”
Section: Introductionmentioning
confidence: 99%